Using a Preceptor Development Series in Writing and Publication to Improve Residency Research Manuscripts - Daniel Longyhore; Eric Wright; Sarah Krahe-Dombrowski; Benjamin Andrick (University of Minnesota Libraries Publishing, 2024)
Description of the Problem: Rates of pharmacy residency research projects making it to peer review and publication are low (between two and seven percent).  Little is known about the influence of preceptor development on moving projects to peer-review and publication.  The Innovation: The primary objective was to describe the effect of a preceptor development series on writing and overall manuscript quality leading to submission to a peer-reviewed publisher.  Three pharmacy preceptors assigned to a post-graduate year 1 residency project were enrolled in a six-week series focused on writing, peer-reviewed publishing, and advancing resident research to publication.  Each preceptor was tasked with implementing development series content in their resident research mentorship.  Critical Analysis: Resident project manuscripts were assessed using a previously published 34-item evaluation tool.  All papers were blinded for independent evaluation by two investigators.  Nine papers were evaluated: three from preceptors who participated in the development program and six from preceptors who did not participate.  The mean summary scores for papers with preceptors who participated versus those who did not were 5.8 and 5.4, respectively, on a 10-point scale.  Additionally, papers from preceptor participants were noted to achieve satisfactory scores on evaluation tool items 85.3% of the time versus 74.7% of the time for non-participants.  Next Steps: Participation in a six-week preceptor development program on advancing resident writing and research to publication provided preceptors the tools needed to mentor higher quality manuscripts ready for publication.  Residency programs may consider designing and implementing such a series to promote preceptor and resident research publication.